Antioxidant rich flavonoids from Oreocnide integrifolia enhance glucose uptake and insulin secretion and protects pancreatic β-cells from streptozotocin insult - Ansarullah; Bharucha Bhavna; Dwivedi Mitesh; Laddha Naresh C; Begum Rasheedunnisa; Hardikar Anandwardhan A; Ramachandran AV (BMC, 2011)
Abstract Background Insulin deficiency is the prime basis of all diabetic manifestations and agents that can bring about insulin secretion would be of pivotal significance for cure of diabetes. To test this hypothesis, we carried out bioactivity guided fractionation of Oreocnide integrifolia (Urticaceae); a folklore plant consumed for ameliorating diabetic symptoms using experimental models. Methods We carried out bioassay guided fractionation using RINmF and C2C12 cell line for glucose stimulated insulin secretion (GSIS) and glucose uptake potential of fractions. Further, the bioactive fraction was challenged for its GSIS in cultured mouse islets with basal (4.5 mM) and stimulated (16.7 mM) levels of glucose concentrations. The Flavonoid rich fraction (FRF) was exposed to 2 mM streptozotocin stress and the anti-ROS/RNS potential was evaluated. Additionally, the bioactive fraction was assessed for its antidiabetic and anti-apoptotic property in-vivo using multidose streptozotocin induced diabetes in BALB/c mice. Results The results suggested FRF to be the most active fraction as assessed by GSIS in RINm5F cells and its ability for glucose uptake in C2C12 cells. FRF displayed significant potential in terms of increasing intracellular calcium and cAMP levels even in presence of a phosphodiesterase inhibitor, IBMX in cultured pancreatic islets. FRF depicted a dose-dependent reversal of all the cytotoxic manifestations except peroxynitrite and NO formation when subjected in-vitro along with STZ. Further scrutinization of FRF for its in-vivo antidiabetic property demonstrated improved glycemic indices and decreased pancreatic β-cell apoptosis. Conclusions Overall, the flavonoid mixture has shown to have significant insulin secretogogue, insulinomimetic and cytoprotective effects and can be evaluated for clinical trials as a therapeutant in the management of diabetic manifestations.